A study on the behavioural intention to use an e-wallet among students of Universiti Malaysia Kelantan in Pengkalan Chepa - Sashitharan Rajamani; Lim Kar Huay; Nur Amirah Junaidy; Nurul Husna Nadzri (2023)
The purpose of this study to investigate a study on the behavioural intention to use an E-Wallet among students of Universiti Malaysia Kelantan in Pengkalan Chepa. This study contributes to define on the behaviour that can intention to use an E-Wallet among students of UMK, while also providing reference to the society about the influenced level of on the behaviour that can intention to use an E-Wallet among students of UMK. The independent variable of this study is perceived usefulness, perceived ease of use, trust, enjoyment, and lifestyle compatibility, whereas the dependent variable is behavioural intention to use an E-Wallet. In addition, this study is founded on two underpinning theories which is Technology Acceptance Model and The Unified Theory of Acceptance Use of Technology. The questionnaire, which consisted of 30 questions were distributed to 364 respondents and received all the feedbacks. Based on the finding, there is a positive and significant relationship between perceived usefulness, trust, enjoyment, and lifestyle compatibility with intention to use an E-wallet. There are various implications and limitations for this research that need to enhance for further research. This study could be a reference to the future previous study that are going to conduct research in the same field. This study is also affected to the user among Universiti Malaysia Kelantan in Pengkalan Chepa who have not used the E-Wallet after reading this thesis and there will be a positive to them.